A CONCEPTUAL MODEL OF SUCCESSION PLANNING FOR PUBLIC HIGHER LEARNING INSTITUTIONS IN MALAYSIA - Bano, Yasmeen (Journal of Techno-Social, 2018)
Succession planning is a very popular topic in all types of organizations nowadays and it is essential to the future survival of public institutes in Malaysia. Succession planning in public Higher Learning Institutions (HLIs) in Malaysia is a new issue and the institutions do not actively engage in it yet. Sometimes succession planning has taken place in the institutions, but it is rarely practiced. This paper will give more attention to the implementation of current best practices of succession planning in the public HLIs in Malaysia and will propose a conceptual succession planning model based on the systematic literature review. The appropriate research method for this study is qualitative approach. This study will experience applying systematic literature and preliminary in-depth interview technique.